A design methodology incorporating user requirements and preferences for a successful product / Hassan Alli - Hassan, Alli (2015)
The failure of most new products on the market is almost always caused by the inability to integrate user requirements and preferences in the development of a product. It has been proven that involving the user in the development of a new product results in the success of the product. This should be done in the product definition stages of the design process, particularly in the development of the specification and characteristics of the product. Involving the user opens up possibilities for new ideas, improves product innovation, decreases the product risks, prevents it from being irrelevant and makes it pleasurable for the product designer to verify the product requirements. The aim of this research is to develop a design methodology for identifying the product characteristics that satisfy the user requirements and preferences, and increasing the probability of its success. A survey was carried out in order to establish the relationship between the product designer and the user during the product development process. In particular, the study seeks to determine the role of the main stakeholders in the success of a new product. The survey consisted of a questionnaire and structured interviews to explore product development activities and decision-making practices during the product definition stages of the design process. Seven successful product characteristics were established from past successful products; namely, multi-function, advanced technology, good performance, good brand, good design, user-friendly and environmentally friendly. It was also found that there are twenty-seven requirements of product design that can be defined in a product design specification. Thirteen requirements are recognized as functional requirements followed by fourteen aesthetical requirements. Both of which contribute to the establishment of successful product design characteristics. In addition, these requirements serve as an indicator of the degree of user satisfaction. This was proven through a product user survey and technical specification analysis. A case study was conducted in which factor analysis of sales performance through a correlation and regression test also showed that the seven characteristics have a strong influence on the success of a mobile smart phone.